2023
DOI: 10.1021/acscentsci.3c00146
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonated Ionomers of Intrinsic Microporosity with Partially Ordered Structure for High-Temperature Proton Exchange Membrane Fuel Cells

Abstract: High mass transport resistance within the catalyst layer is one of the major factors restricting the performance and low Pt loadings of proton exchange membrane fuel cells (PEMFCs). To resolve the issue, a novel partially ordered phosphonated ionomer (PIM-P) with both an intrinsic microporous structure and proton-conductive functionality was designed as the catalyst binder to improve the mass transport of electrodes. The rigid and contorted structure of PIM-P limits the free movement of the conformation and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Sun et al presented the synthesis of a novel phosphonated ionomer of intrinsic microporosity (PIMÀ P, Figure 1f). [19] This polymer was designed for better mass transport in electrodes, which was strongly related to fuel cell performance. The proton conductivity of PIMÀ P was 74 mS cm À 1 at 160 °C under humidified conditions.…”
Section: High Temperature Proton Exchange Membrane Fuel Cells (Ht-pem...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al presented the synthesis of a novel phosphonated ionomer of intrinsic microporosity (PIMÀ P, Figure 1f). [19] This polymer was designed for better mass transport in electrodes, which was strongly related to fuel cell performance. The proton conductivity of PIMÀ P was 74 mS cm À 1 at 160 °C under humidified conditions.…”
Section: High Temperature Proton Exchange Membrane Fuel Cells (Ht-pem...mentioning
confidence: 99%
“…[16] Copyright 2020 Springer Nature). (f) Synthetic pathway to phosphonated poly(pentafluorophenylalkane) [19] (Copyright The authors. Published by American Chemical Society (2023)).…”
Section: Applicationmentioning
confidence: 99%
“…A high current density up to 15.17 A cm –2 at 2.0 V was even achieved by an AEM electrolyzer using the cross-linked catalyst layer. Zhang, Zheng, and co-workers developed a phosphonated ionomer featuring an intrinsic microporous framework and durable proton-conductive −PO 3 H 2 groups . As a high-performance catalyst binder, the ionomer helps to construct stable mass transport pathways to enhance the electrode performance for high-temperature PEM fuel cells.…”
Section: Electrochemical Conversion Beyond Electrocatalystsmentioning
confidence: 99%
“…[33] More recently, they have been also exploited in electrochemical applications [18,34] as in electrocatalysis. For instance, Sun et al [35] reported a novel ionomer based on the strategical incorporation of fluorinated and phosphonated groups in the PIM's local side chains, resulting in promising performances when added to MEA. Particularly, a lower mass transfer resistance was observed with a peak power density much greater than those of commercially available porous binders.…”
Section: Introductionmentioning
confidence: 99%